Determination of ciprofloxacin in Jiaozhou Bay using molecularly imprinted solid-phase extraction followed by high-performance liquid chromatography with fluorescence detection. Issue 1 (15th October 2016) - Lian, Ziru; Wang, Jiangtao
Abstract: A high selective pre-treatment method for the cleanup and preconcentration of ciprofloxacin in natural seawater samples was developed based on molecularly imprinted solid-phase extraction (MISPE). The ciprofloxacin imprinted polymers were synthesized and the characteristics of obtained polymers were evaluated by scanning electron microscopy, Fourier transform infrared spectroscopy and binding experiments. The imprinted materials showed high adsorption ability for ciprofloxacin and were applied as special solid-phase extraction sorbents for selective separation of ciprofloxacin. An off-line MISPE procedure was optimized and the developed MISPE method allowed direct purification and enrichment of the ciprofloxacin from the aqueous samples prior to high-performance liquid chromatography analysis. The recoveries of spiked seawater on the MISPE cartridges ranged from 75.2 to 112.4% and the relative standard deviations were less than 4.46%. Five seawater samples from Jiaozhou Bay were analyzed and ciprofloxacin was detected in two samples with the concentrations of 0.24 and 0.38 μg L − 1, respectively. Highlights: Ciprofloxacin molecularly imprinted polymers (Cip-MIPs) were prepared. The characteristics and recognition efficiency of MIPs were studied. An off-line method for Cip was developed using MIPs as solid-phase extraction. Cip in five seawater samples from Jiaozhou Bay of China was determined.